Evaluation of Violence Against Women With Physical Disabilities in Michigan, 2000-2001 - Milberger, Sharon ([Verlag nicht ermittelbar], 2002)
In the past few years it has become alarmingly clear that women with disabilities are at an extremely high risk for emotional, sexual, and physical assault. The Developmental Disabilities Institute at Wayne State University, in collaboration with the United Cerebral Palsy Association in Michigan, conducted a one-year study to investigate the prevalence and correlates of, and service system capacity related to, domestic abuse among women with physical disabilities in Michigan. The study aimed to address the following research questions: (1) What is the prevalence of domestic violence among a sample of women with physical disabilities? (2) What potential factors for domestic violence exist among women with physical disabilities? and (3) What is the capacity of existing support programs (e.g., safe houses, shelters, and service agencies) to assist women with physical disabilities? The population for this study was women over the age of 18 who had physical disabilities. Consistent with the work of other researchers, physical disabilities in this study were defined as those disabilities that result in functional impairment, such as cerebral palsy, post-polio syndrome, spina bifida, amputation, rheumatic conditions, multiple sclerosis, spinal cord injury, traumatic brain injury, visual impairment, hearing impairment, and stroke. A sample of 177 women was recruited through several mechanisms. To address the question of domestic abuse prevalence, the women participating in the study were first asked to complete a brief questionnaire addressing demographic characteristics and their experience with domestic violence (Part 1, Screening Interview Data). Fifty-six percent (100) of the 177 women interviewed indicated a positive history of abuse at their initial screening. In order to address the second research question about the correlates of abuse, this subsample of 100 women was invited and encouraged to participate in the second phase of the research, which involved a more extensive interview (Part 2, Abuse Interview Data). The interview used was based on a protocol developed by Nosek (1995) that addressed demographic characteristics, social networks, and abuse history. Variables in Parts 1 and 2 include type of disability, type of personal assistance needed, and whether the respondent was ever physically, emotionally, or sexually abused. Part 2 also contains variables on sources of monthly income, who perpetrated the abuse, the abuser's gender, how long the victim knew the abuser, whether the victim sought assistance from a domestic violence program or shelter, and a description of the worst incident of physical abuse. Demographic variables in Parts 1 and 2 include ethnicity, age, employment status, and marital status.